2015
DOI: 10.3201/eid2106.141797
|View full text |Cite
|
Sign up to set email alerts
|

Oral Cholera Vaccine Coverage, Barriers to Vaccination, and Adverse Events following Vaccination, Haiti, 20131

Abstract: Coverage was comparable to or higher than that in other countries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
36
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 23 publications
4
36
0
1
Order By: Relevance
“…Some reasons for partial and non-acceptance of OCV such as lack of time and fear of side effects were consistent with reasons found in other settings and with reasons captured in WHO's vaccine coverage survey data from the PoCs [5][6][7]. These reasons are increasingly important aspects of research on vaccination uptake as public perceptions have led to declines in rates of routine vaccination, and to barriers to the introduction of new vaccinations [9,10].…”
Section: Discussionsupporting
confidence: 65%
See 3 more Smart Citations
“…Some reasons for partial and non-acceptance of OCV such as lack of time and fear of side effects were consistent with reasons found in other settings and with reasons captured in WHO's vaccine coverage survey data from the PoCs [5][6][7]. These reasons are increasingly important aspects of research on vaccination uptake as public perceptions have led to declines in rates of routine vaccination, and to barriers to the introduction of new vaccinations [9,10].…”
Section: Discussionsupporting
confidence: 65%
“…Fear of illness from combining the vaccine with alcohol and the perception of alcohol as a means for personal resilience affected decisions. The problem of alcohol abuse in conflict-affected populations warrants further study since it relates to behaviors that lead to greater risk of cholera and as a potential contributor to lower rates of vaccination among men [5,6,12].…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…This finding suggests a need to remind vaccine recipients to bring back vaccination cards for the second round and to improve vaccination card recording training for vaccination teams. Previous OCV campaigns in Haiti that reported higher card-documented 2-dose coverage (51%–70%) emphasized the value of keeping vaccination cards for receiving the second vaccine dose ( 21 ). Where feasible, the use of serologic studies may also be helpful in validating reported coverage.…”
Section: Discussionmentioning
confidence: 99%